(untitled) (American Journal of Islam and Society, 2013)
Many women are exposed to domestic and/or sexual violence by their family members on a global scale, forced to marry before reaching maturity, mutilated for the sake of preserving their chastity, and deprived of their right to education and of any inheritance rights. Honor-related violence is an extreme, worldwide form of violence that after 9/11 has been increasingly associated with Islam, as if it were perpetrated only by Muslims living either in diaspora communities or in Muslim-majority countries. This stereotyping has lent ideological support to unequal power relations that have been shaped mainly by western economic interests since colonialism. This essay contextualizes honor-related violence in relation to patriarchy and a society’s economic wellbeing, to migratory experience in terms of multicultural politics and, finally, to critiques its use in post-9/11 misrepresentations of Islam. It argues that unequal power relations and patriarchal domination, as opposed to religion, shape this global phenomenon.